هيمنة طالبان في الرواية "عداء الطائرة الورقية" لخالد حسيني من خلال انطونيو غرامشي - وحي هدايتي; أحمد خليل; فيني رسفاتي يوريسا (Prosiding Konferensi Nasional Bahasa Arab, 2017)
Abstract: The Taliban hegemony is illustrated in the novel The Kite Runner. The Taliban's hegemony had an impact on the emergence of a series of human rights abuses in Afghanistan. Hegemony is domination by a group to another group with or without threat of violence so that ideas dominated by dominant group to dominated group can be accepted. The kite runner is the first novel by kholed husein.This novel tells about the friendship of two Afghan children wrapped in their country due to the conflict of the Soviet invasion. This novel describes the many conflicts caused by the invasion of the Soviet Union and the Taliban regime.This research is a qualitative research. The formulation of the problem in this study is how the condition of Afghanistan in the novel the Kite Runner and how the form of Taliban hegemony in the novel The Kite Runner. The data source in this research is novel The Kite Runner. Data collection techniques use reading techniques and techniques to record. While the analytical technique used is the technique of Miles and Huberman model analysis. The results of this study are: 1) Taliban hegemonic form in the film The Kite Runner is the spread of ideology in the form of a weekly lecture launched by Taliban officials, hegemony, Moral leadership, culture, supremacy; 2)  Taliban hegemony to Afghanistan is the Taliban wants to liberate Afghanistan from Soviet invasion and the Taliban wants to restore the glory of the Folk tribe in Afghanistan by expelling some minority tribes, such as the Hazaras; 3) the impact of Taliban hegemony on Afghanistan is the state of Afghanistan after Taliban hegemony is the rapid growth of poverty, the emergence of orphans, disabled victims and uncertain political circumstances.                                                                                               الكلمات الرئيسية: هيمنة, الطالبان , الأيديولوجية,  أفغانستان.